COMBINED SURGERY OF SPREAD THYROID CANCER - V. Zh. Brzhezovsky; M. V. Lomaya (Опухоли головы и шеи)
Results of treating of 99 patients with differentiated thyroid cancer spreading beyond the capsule of the organ were analysed. In most cases with spreading the tumor to the tracheal rings performing of organ-preserving operations (from “window-like” tracheal resections to circular tracheal resection with intertracheal anastomosis) is possible. Choosing of type of operation to be performed depends on localisation and spread of tumor invasion of trachea, pharynx and esophagus. Using of combined operations in patients with locally-spread thyroid cancer allows to achieve long and stable remission in most of the cases.